Pityriasis rubra pilaris/Follicular psoriasis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2000)
Pityriasis rubra pilaris is a rare disease, which is included among follicular eruptions. It is well characterized from a clinical point of view. However, its etiology is unknown and a well defined biological or pathological marker lacks. From a clinical point of view, pityriasis rubra pilaris is characterized by palmo-plantar keratoderma, follicular keratosis and tendency to erythroderma. Psoriasis is very frequent and is easily diagnosed in the majority of cases. However, psoriasis can be rarely characterized by clinical features superimposable to those ones of pityriasis rubra pilaris, namely involvement of the palmo-plantar region, follicular keratosis and tendency to erythroderma.